Study of behavior on Na activated Ca-bentonite of Maghnia by free swell index test treated cement and Swell potential of clays of Mars El Kebir treated pozzolan - Boualla, N.; Adjdir, M. (Algerian Journal of Research and Technology (AJRT), 2017)
In this article, we will discuss about affinity adsorption of Ca2+ and Na+ by bentonite. It is known that the exchangeable cation used in many studies is the Na+ cation because its use increases the basal space of the bentonite that becomes very large. In addition, this study includes the influence of additions on the mechanical behavior of clay swelling. Two types of soils have been studied: Mers El Kebir clay, and Maghnia bentonite. The results shows that the mechanical behavior of the Mers El Kebir clay show that there is a significant decrease of the swelling potential with the increase of the pozzolanic addition. The cement has a very high efficiency on the swelling of bentonite and has a significant effect on the rate of the swelling potential and on the Atterberg limits.